The Effect of the Teams Games Tournament (TGT) Model and Motivation on Understanding Pancasila Philosophy - Suryanto, Hadi; Ghofur, Abd; Zaman, Akhmad Qomaru (research, training and philanthropy institution Natural Aceh, 2024)
The effect of the Teams Games Tournament learning model and motivation on understanding the ideology of Pancasila in the Civics Study Program was studied using a non-equivalent group pretest-posttest research design. The PPKN study program, totalling 30 people, was the subject of this research. Questionnaires and tests are used to gather information about research findings. The research investigation was carried out using the independent sample t-test technique, with a significance level 0.05. The study's findings show that the total count is 5.509. Here, the t value exceeds the 2.048 t table value. These findings suggest that cooperative learning models of the TGT kind effect student learning motivation. Based on the Independent Samples Test on